Exploring Indonesia’s Diaspora Branding through Healthcare: A Gendered Communication Perspective in Perth, Australia - Ramonita, Latifa; Husada, Safaruddin; Yunus, Ulani; Moannissa, Anggi; Keliat, Cynthia (Sawwa: Jurnal Studi Gender, 2025)
Healthcare professionals, especially Indonesian women health workers in Perth, Australia, play a important role as unofficial cultural ambassadors in the diaspora. This study examines how Indonesian women in Perth's healthcare industry negotiate their identities as women, migrants, and medical professionals and demonstrate cultural values, using qualitative methodology, with social identity theory and transnational feminist as the theoretical framework. Interviews were conducted to Indonesian women healthcare workers in Perth, as the study prioritizes depth, experiential richness, and identity negotiation, consistent with exploratory qualitative and phenomenological approaches. The results demonstrate how participants build interpersonal communication and multicultural engagement by incorporating Indonesian values—such as empathy, collectivism, and cultural sensitivity—into patient care. These women exhibit perseverance that supports Indonesia’s branding in healthcare, their resilience in overcoming challenges related to language and maintain work-life balance. The findings highlight the significance of communication in shaping national identities in diverse environments and contribute to the understanding of gendered diaspora experiences.